PELATIHAN PENINGKATAN INOVASI WIRAUSAHA STARTUP PADA PONDOK PESANTREN AL HIKMAH BANJARMASIN - Rahmi Widyanti; Aida Vitria; Husnurrofiq Husnurrofiq; Basuki Basuki (Universitas Islam kalimantan MAB, 2024)
Business startup that is run both small and large with digital platform aims to make a profit. To find out the extent of the benefits derived from the business startup that is run requires careful managing. Managing of business startup is expenses and income must be done carefully so that the analysis and calculation of profit and loss of the business carried out with results that reflect the business potential. Banjarmasin City are many schools including Pesantren Al Hikmah, a river cultural area, where most of the population (52%) live in small business fields and most (48%) of them (families) depend their livelihoods / livelihoods from the sea as traditional trading. Finally, there has been an outreach and counseling about designing businesses startup by a group of students, but it has not provided adequate results. This is due to not doing a good business startup. Through community service activities it seeks to provide knowledge about how to manage their business with low price of a product so that it can benefit the producers.